Electric vehicles fire protection during charge operation through Vanadium-air flow battery technology - L. Barelli; G. Bidini; P.A. Ottaviano; D. Pelosi; M. Perla; L. Trombetti; F. Gallorini; M. Serangeli (Heliyon, 2021)
During the last decade, electric vehicles had a remarkable diffusion caused by Li-ion batteries lowered prices and improved performances. Meanwhile, incidents involving fire were reported for electric vehicles during charge operation or simple parking. The potential drawbacks of this technology could play a role on safety in the next years, especially for household or underground charge. This paper presents the development of a novel system concept based on a Vanadium-air flow battery, applied to provide charge and fire safety of electric vehicles through oxygen reduction in a sealed box. When the vehicle is parked inside the box and the passengers are outside of it, a nitrogen injection is operated to reduce the fire risk quickly, during the subsequent vehicle charge operation the oxygen is consumed from the box atmosphere by the cathode of the Vanadium-air battery that supplies energy, then the nitrogen reserve is restored consuming oxygen from the external ambient and the energy output can be supplied to smart grids. The system is mainly composed by the Vanadium-air flow battery, the protection box and the nitrogen reserve, it is sized relatively to the most diffused road and commercial electric vehicles for different values of on-board battery capacity and charge power Moreover, it can be integrated into vehicle-to-grid energy systems improving intersectoral flexibility.